1982
DOI: 10.1007/bf00387207
|View full text |Cite
|
Sign up to set email alerts
|

Frequency limitations of the two-point central difference differentiation algorithm

Abstract: A two-point central difference algorithm is often used to calculate the derivative of a function. This estimate is only valid over a limited frequency range. Therefore, the algorithm can be modeled as an ideal differentiator in series with a low-pass filter. The filter cutoff frequency is a function of the time between the points. We discuss the accuracy and limitations of using this algorithm on human saccadic eye movement data. To calculate the velocity of saccadic eye movements the algorithm should have a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 2 publications
0
59
0
Order By: Relevance
“…Finally, the reduction in peak velocities reported here is a best-case estimate as we made sure that the actual time of the peak velocity coincides with a sample. Since this time is a one-point measure, it can easily be missed by an eye tracker during a real measurement (Andersson, Nystrom, & Holmqvist, 2010), resulting in further lowered peak velocities (Bahill et al, 1982). Therefore the reduction in peak velocities for lower sampling rates reported here might even be worse for real data.…”
Section: The Effect Of Sampling Ratementioning
confidence: 91%
See 2 more Smart Citations
“…Finally, the reduction in peak velocities reported here is a best-case estimate as we made sure that the actual time of the peak velocity coincides with a sample. Since this time is a one-point measure, it can easily be missed by an eye tracker during a real measurement (Andersson, Nystrom, & Holmqvist, 2010), resulting in further lowered peak velocities (Bahill et al, 1982). Therefore the reduction in peak velocities for lower sampling rates reported here might even be worse for real data.…”
Section: The Effect Of Sampling Ratementioning
confidence: 91%
“…It has been shown that a one-sample, two-point central difference (2pCD) method is ideal for this purpose (Bahill, Kallman, & Lieberman, 1982). Importantly, this method produces no lag in the velocity channel with respect to the position channel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A two-point central difference differentiation algorithm (Bahill, Kallman, & Lieberman, 1982) continuously estimated the momentary eye velocity and generated a trigger signal indicating the occurrence of a saccade once the velocity exceeded 15º/sec. We verified that the trigger-induced target blanking or target shift consistently occurred in the first third of the duration of the saccade.…”
Section: Apparatus and Stimulimentioning
confidence: 99%
“…Thus the oculometer did not limit the frequency content of these smooth pursuit eye movements. However an FFT analysis of saccadic eye movements has shown information up to 40 Hz (Bahill, et al, 1982).…”
Section: Methodsmentioning
confidence: 99%